TINJAUAN HUKUM ISLAM TENTANG WAKAF WASIAT (STUDI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 41 TAHUN 2004 TENTANGWAKAF) - Ahmad Irwan Zendrato (Fakultas Agama Islam, 2021)
Islamic law is a law that comes from the teachings of Islam and is part of the Islamic religion. Law Number 41 of 2004 is a regulation that regulates waqf issues. not yet certified in Sooko District according to Islamic Law and Law Number 41 of 2004. Nadzir in this case has the authority to carry out administrative processes and manage waqf land that has not been certified. The formulation of the problem in this study are: (1) how is the legal review of fiqh regarding will waqf in Law Number 41 of 2004. (2) how is the review of the authority of nadzir waqf testament Law No. 41 of 2004. (3) how is the review of the compilation of Islamic law regarding testamentary waqf in Law number 41 of 2004. The type of research conducted by the author is a field research using qualitative methods , while the data collection techniques used were interviews and documentation. The analysis used using the deductive method, namely the discussion that begins by stating the arguments, theories or provisions that are general in nature. alaih, and sighat. Meanwhile, according to Law Number 41 of 2004 Article 41 Paragraph (3) Waqf assets whose status has been changed due to the exception provisions as referred to in paragraph (1) must be exchanged for assets whose exchange value benefits are at least the same as the original waqf assets. Second, the authority of Nadzir over uncertified waqf land according to the Compilation of Islamic Law Article 220 Paragraph (1) Nadzir is obliged to manage and be responsible for the waqf wealth and its results, and the implementation of the waqf in accordance with the objectives according to the provisions regulated by the Minister of Religion. Law No. 41 of 2004 Article 11 Nadzir has the task of administering waqf assets, managing and developing waqf assets in accordance with their objectives, functions, and designations.